KONFIGURASI UNSUR-UNSUR KEBUDAYAAN DALAM BUKU TEKS SEJARAH KEBUDAYAAN ISLAM MADRASAH TSANAWIYAH SESUAI DENGAN KURIKULUM 2008 - Rofik Rofik (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2016)
Nowadays, information and science are abundantly available. Therefore, we need to select the materialswhich are really benefical for student. As one of subjects in the Islamic school curricula, the history ofislamic culture that are in line with the ideal demands, as are formulated in the content standards. Inpractice, the formulation is expressed within textbooks. However, people’s understanding of the subjectof the history of islamic culture is sometimes stigmatized that history of islamic culture materialsshould be the politics. Thus, this study finds its urgency for readers understanding that in accordancewith the 2008 curriculum, the prominent materials are moral, belief system, efforts and habits, insteadof politics.Keywords: Cultural Elements, Textbooks of The History of Islamic Culture.